(untitled) (Cadernos de Sociomuseologia, 2024)
The present work weaves a dialogue between Urban Art and Sociomuseology at Quinta do Mocho, the Largest Open Air Art Gallery in Europe and one of the largest in the world, from the perspective and experience between the residents of this community and the researchers/ authors.The art space is problematized through participatory observation and the affective relationship and mutual learning built between those who intertwine, reinforcing the important role of urban art that reframes this space and weaves dialogues that record other perspectives of the present and future, of the that Paulo Freire conceptualizes as viable unprecedented: overcoming limit situations and the consequent transformation of this situation through action. Art appears here as a record of a community fighting for the preservation of its multiple culture, reconfiguring public space and including artists and the community, a liberating action in struggle that draws the attention of Sociomuseology. Keywords: Urban- Art- Unpublished-Viavel-Dialogue-Transformation